2001
DOI: 10.1073/pnas.012611099
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of Renilla luciferase reporter gene expression in living mice

Abstract: Imaging reporter gene expression in living subjects is a rapidly evolving area of molecular imaging research. Studies have validated the use of reporter genes with positron emission tomography (PET), single photon emission computed tomography (SPECT), MRI, fluorescence with wild-type and mutants of green fluorescent protein, as well as bioluminescence using Firefly luciferase enzyme͞protein (FL). In the current study, we validate for the first time the ability to image bioluminescence from Renilla luciferase e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
340
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(346 citation statements)
references
References 23 publications
6
340
0
Order By: Relevance
“…In addition, there are difference in animal batches, clonal selections, transfection efficiency and levels of gene expression in different cells. It was interesting to note that unlike bioluminescent signals, 31 which tapered within 2 h, the signal in these NTR tumors often persisted overnight. Such unique capabilities can open up many new applications in the areas of gene imaging and cell tracking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are difference in animal batches, clonal selections, transfection efficiency and levels of gene expression in different cells. It was interesting to note that unlike bioluminescent signals, 31 which tapered within 2 h, the signal in these NTR tumors often persisted overnight. Such unique capabilities can open up many new applications in the areas of gene imaging and cell tracking.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17]19,20 Firefly luciferase gene expression has been monitored in transfected cell implants 19,20 and after delivery by viral vectors. 14,16 Recently, Iyer et al 18 have shown the first example of bioluminescent imaging of liposomal gene delivery, but polycationic gene delivery using a targeted vector complex has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…We are also validating more sensitive optical repoter genes such as a synthetic renilla luciferase, which should lead to a log order more sensitivity. 20 With continued improvement in sensitivity of detection, formulations with very low efficiency should be able to be utilized with noninvasive optical CCD imaging. This is the first study to directly compare these PEI formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The luciferases from Renilla and firefly have different substrates, coelenterazine and D-luciferin, respectively, and can be imaged in tumors in the same living mouse with kinetics of light production being separable in time by separate injections of these two substrates. 88 Recently, dual bioluminescence imaging has been used to monitor gene delivery via a therapeutic vector and to follow the effects of the therapeutic protein TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) in gliomas. 70 Glioma cells stably expressing Fluc were implanted subcutaneously into nude mice and the tumor growth was monitored in vivo over time by luciferin administration and BLI.…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%